2020
DOI: 10.1024/1012-5302/a000704
|View full text |Cite
|
Sign up to set email alerts
|

Übereinstimmung des Advanced Nursing Process mit Beobachtungen, Interviews und Pflegedokumentationen im Akutspital

Abstract: Zusammenfassung. Hintergrund: Pflegefachpersonen mit guter klinischer Entscheidungsfindungskompetenz stellen genauere Pflegediagnosen, setzen wirksamere Pflegeinterventionen um und erzielen bessere pflegesensitive Patientenergebnisse. Studien haben gezeigt, dass die Inhalte der Pflegedokumentationen manchmal nicht mit den Berichten von Patientinnen und Patienten und Pflegefachpersonen übereinstimmen. Fragestellung: Inwieweit stimmen die dokumentierten Pflegediagnosen, -interventionen und ‑ergebnisse mit beobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Our results could be the consequence of a more accurate patient assessment and nursing diagnosis. Previous studies have demonstrated that using a problem‐oriented approach was one of the potential solutions to the lack of critical thinking and clinical reasoning (Leoni‐Scheiber et al, 2020; Paans et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Our results could be the consequence of a more accurate patient assessment and nursing diagnosis. Previous studies have demonstrated that using a problem‐oriented approach was one of the potential solutions to the lack of critical thinking and clinical reasoning (Leoni‐Scheiber et al, 2020; Paans et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Research about SNL and the related Advanced Nursing Process describes that interventions are effective when correctly formulated according to classification systems. This SNL makes interventions and patient-centred outcomes comparable and enables evaluation [44,45]. Since nutritional interventions affect several levels, three additional components of effective interventions were defined on a meta-level, according to a first analysis of the literature: staff training, multi-component measures and interprofessional food promoting culture [46,47].…”
Section: Synthesismentioning
confidence: 99%
“…Although healthcare providers work in reputable surgical centers and position patients in order to prevent lesions, these events are more frequent than desired (Burlingame, 2017; Kimsey, 2019; Tallier et al., 2017). Pressure injuries are the most described event in the literature, with an incidence that varies between 10% and 77% (Buso et al., 2021).…”
Section: Introductionmentioning
confidence: 99%